Evaluating the Obstetrical Implications of Antenatal Testing for Women with Morbid Obesity: Maternal and Fetal Outcomes of Increased Surveillance - Edelson, P. Kaitlyn (Am J Perinatol, 2016)
OBJECTIVES: Despite limited data, antenatal testing has been initiated in many institutions for women with morbid obesity given their increased risk of stillbirth. Therefore, our objective was to evaluate the obstetrical implications of antenatal testing in the morbidly obese population. STUDY DESIGN: We performed a retrospective cohort study of women undergoing antenatal testing from January 2011 through December 2012 who delivered at our institution. The exposed group was women undergoing antenatal testing with morbid obesity (body mass index [BMI] ≥ 40 kg/m(2)). This group was subdivided into two groups: group 1, which included women undergoing testing for morbid obesity alone, and group 2, which included women undergoing testing for morbid obesity with an additional medical comorbidity. The unexposed group (group 3) comprised nonmorbidly obese women (BMI < 35 kg/m(2)) undergoing antenatal testing for similar medical comorbidities. Our primary outcomes were induction of labor and gestational age at delivery. RESULTS: A total of 512 women met inclusion criteria. Group 1 had a lower induction rate as compared with groups 2 and 3 (22.2, 32.5, and 37.6%, respectively; p = 0.003). Additionally, women delivered at a later gestational age in group 1 (39.3 weeks [38.4–40.2]) compared with groups 2 (38.5 weeks [36.1–40.3]) or 3 (37.1 weeks [37.0–38.2]), p = 0.04. There were no significant differences in our secondary outcomes including rate of cesarean delivery (p = 0.11) or rate of nonreactive nonstress test (p = 0.4). CONCLUSIONS: While it remains unknown whether antenatal testing decreases the stillbirth risk in morbidly obese women, this population does not appear to be at increased risk of induction of labor or delivery prior to 39 weeks secondary to testing. Future studies should evaluate neonatal implications and cost-effectiveness of antenatal testing in this group.